Effects of the polysaccharide beta-glucan on clastogenicity and teratogenicity caused by acute exposure to cyclophosphamide in mice - Oliveira, Rodrigo Juliano; Sparca Salles, Maria Jose; da Silva, Ariane Fernanda; Nakamura Kanno, Tatiane Yumi; dos Santos Lourenco, Ana Carolina; Freiria, Gabriele Antico; Matiazi, Hevenilton Jose; Ribeiro, Lucia Regina [UNESP]; Mantovani, Mario Sergio (Academic Press Inc. Elsevier B.V., 2009)
Alterations that could lead to the cancer development may also be related to an adverse development of offspring in experimental animals. Some functional foods, which contain the polysaccharide beta-glucan, have been described as being effective in the prevention of clastogenic damage. Based on that finding, the aim of the present study was to determine the efficacy of this sugar polymer in the mutagenic and teratogenic damage control. Two sets of females, pregnant and non-pregnant, were evaluated. The results indicated that p-glucan was effective in preventing clastogenic damage in pregnant as well as non-pregnant females. In addition, pregnant females were more susceptible to mutagenic damage. However, teratogenic effects were not prevented effectively, although there was a trend toward a reduction in level of malformations. Despite beta-glucan did not prevent malformations, it increased fetal viability and reduced number of post-implantation losses and resorption, thereby enhancing reproductive performance in females. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: beta-Glucan; Teratogenicity; Cyclophosphamide; Mutagenic